Moderasi beragama sebagai basis pembentukan karakter mahasiswa muslim - Aprilia, Anisa (Maliki Interdisciplinary Journal, 2026)
Religious moderation is a balanced and tolerant attitude in practicing religion that avoids extremism, aligned with Pancasila values through four pillars: national commitment, tolerance, anti-violence, and cultural accommodation. Implementation of religious moderation consists of two forms: initial formulation and final formulation. Initial formulation encompasses all functions in the System Requirements Specification (SRS) document of higher education, while final formulation includes all SRS functions with changes or additions through wasathiyah curriculum, interfaith dialogue, cultural festivals, and social media monitoring to prevent digital radicalism. Implementation is carried out through the hidden curriculum ISRA model, Kemenag extracurricular FGD activities, and Religious Moderation Houses. The results form inclusive campuses, reduce intolerance, and strengthen national unity toward Golden Indonesia 2045. Challenges such as conservative resistance and low digital literacy are addressed through lecturer training, new student orientation, and community synergy. Overall, religious moderation plays a role in shaping a tolerant, peaceful, and adaptive generation in the digital era.